On the Meaning of Movement in Music, Development and the Brain. - Phillips-Silver, Jessica (Contemporary Music Review, 2009)
This article is written from the perspective of empirical research within the broad field of the neuroscience of music (including evolutionary, behavioural, neuroimaging and neuropsychological approaches), with a central theme of the multisensory experience of rhythm and movement in music and dance. Section 1 explores some historical theories on the evolutionary origins of music that point to the important role of rhythmic synchronisation. Section 2 discusses some of the concepts of beat perception and synchronisation in the scientific literature, with examples of various methodologies that have been used to measure these abilities in the body and in the brain. Section 3 focuses on the development in infancy of the musical capacity to 'feel the beat', which involves the integration of auditory and movement information. Section 4 takes a neuropsychological perspective, giving examples of what can go wrong in cases of abnormal music development, and posing some provocative questions about whether or not we all 'have rhythm'. These different perspectives, taken together, reflect a scientific interest in understanding music, movement and the brain. The goal of the article is to find points where neuroscience and music meet, while recognising certain limitations. The discussion is meant to complement important studies and observations in the fields of musicology, music pedagogy, music performance and music therapy by providing empirical support for some of the work of experts in these fields. Ultimately, musicians and scientists together can illuminate the importance of music and movement for the human mind.